2017
DOI: 10.1016/j.applthermaleng.2016.08.223
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of non-premixed and partially-premixed combustion simulations in a realistic Tay model combustor

Abstract: A comparative study of two combustion models based on non-premixed assumption and partially premixed assumptions using the overall models of Zimont Turbulent Flame Speed Closure Method (ZTFSC) and Extended Coherent Flamelet Method (ECFM) are conducted through Reynolds stress turbulence modelling of Tay model gas turbine combustor for the first time. The Tay model combustor retains all essential features of a realistic gas turbine combustor. It is seen that the non-premixed combustion model fails to predict the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 28 publications
3
11
0
Order By: Relevance
“…Thus, the flame can be assumed to be very thin, and it can be identified as a laminar flame element, called a flamelet. As highlighted by a previous study [34], the increase in Da with increasing Re is observed due to the fast chemistry (as shown in Figure 7), while the decrease in Da with increasing Re is due to reduction in mixing time since the turbulent intensity and scalar dissipation rate increase with increasing Re.…”
Section: Damköhler Numbers and Combustion Diagramssupporting
confidence: 58%
“…Thus, the flame can be assumed to be very thin, and it can be identified as a laminar flame element, called a flamelet. As highlighted by a previous study [34], the increase in Da with increasing Re is observed due to the fast chemistry (as shown in Figure 7), while the decrease in Da with increasing Re is due to reduction in mixing time since the turbulent intensity and scalar dissipation rate increase with increasing Re.…”
Section: Damköhler Numbers and Combustion Diagramssupporting
confidence: 58%
“…The terms α c and α k can be evaluated using Equations (20) and (21), where ω c , Sc t , and σ t represent progress term, turbulent Schmidt number (0.70), and turbulent Prandtl number (0.85), respectively. 49 The mean reaction rate can be determined using the Zimont Turbulent Flame Speed Closure (ZTFSC) method, 50 as expressed in Equation (22). Where ρ u U t , and C are unburnt mixture density turbulent flame speed, and PV, respectively.…”
Section: Reaction Modelmentioning
confidence: 99%
“…Transport equations for mean mixture fraction and reaction PV are presented in Equations () and (), respectively. The terms αc and αk can be evaluated using Equations () and (), where ωc, Sct, and σt represent progress term, turbulent Schmidt number (0.70), and turbulent Prandtl number (0.85), respectively 49 . The mean reaction rate can be determined using the Zimont Turbulent Flame Speed Closure (ZTFSC) method, 50 as expressed in Equation ().…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Why not use a multi-dimensional computational uid dynamics (CFD) code with a genetic algorithm (GA)to monitor Soot formation , timing to inject gas and diesel and set the nozzle holes for both based on the circumference and the angle incident to the re ected ray that any given sample represents 87 Should we nd out what accelerates ame propagation like ( n -butanol, sec-butanol, and iso-butanol) and what shortens the duration for the combustion and affect particulate number (PN) based on different injection process timings and consume less fuel , less CO, unburnt hydrocarbon , even which can be the attributed to the shift in the local mixture of air owing to highly sooty peninsula with the cooling effect of Exhaust Gas Rate 88 Opening ourselves to having "less energy dissipating turbulence models" {Zimont Turbulent Flame Speed Closure Method (ZTFSC) and Extended Coherent Flamelet Method (ECFM)} such as "scale resolving simulation (SRS)" can work if we able to measure concentration of the species and the pattern of the ame or the temperature closure to the injection model of the combustor 89 Open Cost Modelling If we are serious about the Cost of Obtaining Usable Datasets then we must pay attention to the idea of identifying the "out-of-working range parameters"…”
Section: Patterns Of Machine Operationmentioning
confidence: 99%